Osteosynthesis of fractures after elbow ankylosis treated with an Ilizarov external ring fixator: A case report. (October 2020) - Yanagisawa, Yohei; Kawamura, Tokio; Asakawa, Shunsuke; Yamazaki, Masashi
Abstract: Treatment with an Ilizarov ring external fixator is less invasive of soft tissues than is open reduction and internal fixation (ORIF) surgery. Operative treatment of fractures with an Ilizarov ring external fixator after elbow ankylosis has not been reported. We describe our experience with this surgical treatment (i.e., placement of an Ilizarov external ring fixator) for a fracture that occurred after elbow ankylosis. A 63-year-old Japanese woman fell from standing height onto her left elbow. A transverse fracture was observed at the ankylosed site and the patient underwent surgery 8 days after the injury. The surgery was performed in the prone position under general anesthesia. Four months postoperatively, the fracture showed bone union and the fixator was removed. At the 1-year follow-up, she had no pain and no nerve palsy, can could perform the same activities as before the injury. Thus, treatment with an Ilizarov ring external fixator for a fracture around the elbow joint is a minimally invasive procedure that affords firm fixation and achieves fracture-site compression. Osteosynthesis of fractures after elbow ankylosis treated with an Ilizarov external ring fixator has not been reported previously. This technique was less invasive to the soft tissues and was considered to be a good surgical treatment to achieve osteosynthesis of fractures after elbow ankylosis.